Analisis Strategi Bersaing dalam Meningkatkan Pendapatan Toko Herbal Bukittinggi (Studi Kasus BRC Grosir Herbal Bukittinggi) - Fatma Syafrila Yeni; Awaluddin Awaluddin (ARZUSIN, 2026)
Although competitive strategy in herbal businesses has received attention in several studies, research that specifically discusses the implementation of marketing mix (4P)-based competitive strategies in increasing revenue in local herbal businesses remains limited. This study aims to analyze the competitive strategies implemented by BRC Grosir Herbal Bukittinggi and to identify the supporting and inhibiting factors in increasing business revenue. This study used a qualitative approach with a case study design, involving participants consisting of managers, employees, resellers, and customers selected through a purposive sampling technique. Data were collected through interviews, observation, and documentation, and were then analyzed using an interactive data analysis technique through the stages of data reduction, data display, and conclusion drawing. The findings showed that the competitive strategies implemented included aspects of product, price, place, and promotion, with consultative service and the use of social media as the main advantages. In addition, therapy services, good communication, and product availability were supporting factors for increasing revenue, whereas price competition, economic conditions, and external factors were inhibiting factors. These findings contribute to the development of competitive strategy and marketing theory and broaden understanding of the implementation of the marketing mix in the context of local herbal businesses. The conclusion of this study confirms the importance of optimizing marketing strategies that are adaptive to market dynamics and suggests that business actors improve innovation and promotional effectiveness. The implications of this study include theoretical contributions to the development of the strategic management literature and practical implications for herbal business actors in increasing competitiveness and revenue.